Bibliometric Analysis of Research on ESBL-Producing Escherichia coli in Healthcare Settings - Hakimi, Baslan Fatih; Rachman, Brian Eka; Nabila, Riski (Faculty of Medicine, 2026)
This study mapped the global research landscape on ESBL–producing E. coli in healthcare settings and examined trends in scientific output, major contributors, and thematic focus. Articles indexed in Scopus up to 2025 were analyzed using Bibliometrix (R) and VOSviewer to evaluate publication growth, country and institutional productivity, leading authors, core journals, collaboration networks, and keyword patterns. A total of 4,032 documents were identified, showing substantial expansion since the mid-2000s, especially after 2010. The United States, China, and several European and Asian countries emerged as dominant contributors. Keyword and network analyses revealed a thematic shift from early enzyme-focused studies toward high-risk clones, carbapenemase co-production, therapeutic strategies, and one health–related transmission. Overall, the field appears mature yet continuously evolving, reflecting broader global antimicrobial resistance trends.